Desarrollo de una alternativa para el pretratamiento de la corriente de alimentación al proceso de ósmosis inversa en el tratamiento de lixiviados del relleno de Doña Juana (2020)
The degree project was based on a diagnosis of the Doña Juana Landfill units. Emphasis was placed on the physicochemical treatment line on which our grade work is based. In the diagnosis, the leachate was sampled to determine the parameters that are currently not being met in the plant, taking into account the current environmental regulations: Resolution 631 of 2015. In addition, the operation of the current treatment units was verified by performing analysis statistics according to volumetric capacity; analysis of the behavior of the Ph and the parameters such as BOD, COD and OSH were made.